1977
DOI: 10.1002/1097-0142(197706)39:6<2603::aid-cncr2820390645>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Chronic mastopathy and breast cancer:A Follow-Up Study

Abstract: Over an average period of seven years 2,900 cases of benign breast lesions diagnosed by biopsy between 1948 and 1973 in the Department of Pathology, Kaiser Foundation Hospital, Oakland, were followed for breast cancer development. When classified according to traditional diagnostic categories, the cancer incidence per 1,000 person-years varies between 2.7 and 7.9 and appears to be elevated in comparison to expectations obtained from the Third National Cancer Survey, San Francisco Bay Area. Two thousand four hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

1980
1980
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(32 citation statements)
references
References 10 publications
2
30
0
Order By: Relevance
“…An example of the importance of such adjustment is demonstrated by fibroadenoma. Two studies (26,32) have shown an association between fibroadenoma and increased breast cancer risk, whereas two other studies (21,29) have not. Hutchinson et al (28) reported an elevated risk for women whose fibroadenoma was accompanied by fibrocystic disease, but not for women who had fibroadenoma alone.…”
Section: Estimates Of the Occurrence Of Bbdmentioning
confidence: 81%
See 3 more Smart Citations
“…An example of the importance of such adjustment is demonstrated by fibroadenoma. Two studies (26,32) have shown an association between fibroadenoma and increased breast cancer risk, whereas two other studies (21,29) have not. Hutchinson et al (28) reported an elevated risk for women whose fibroadenoma was accompanied by fibrocystic disease, but not for women who had fibroadenoma alone.…”
Section: Estimates Of the Occurrence Of Bbdmentioning
confidence: 81%
“…Table 2 summarizes the results of studies that have addressed this issue. With two exceptions (18,19) these were prospective studies that followed women with biopsy-defined BBD over time and compared the observed number of breast cancers that developed with the expected number based on the experience of the general population (2,4,(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32).…”
Section: Estimates Of the Occurrence Of Bbdmentioning
confidence: 99%
See 2 more Smart Citations
“…Though none of our cases presented with recurrence or carcinoma within fibroadenoma specimen. Breast cancer risk for fibroadenoma has been estimated at 3.1 annual incidence per 1000, person-year rate, and the relative cancer risk estimated at 7.0 [26][27] . A more recent study designed to delineate the possible correlation between the histologic features of the fibroadenoma and the risk for subsequent breast cancer used the term "complex fibroadenoma."…”
Section: Discussionmentioning
confidence: 99%